65‐3: Green Top‐emission Quantum Dot Light‐emitting Diodes (TE‐QLED) with Normal and Inverted Structure. Issue 1 (25th September 2020) - Lin, Kun-Rong; Lee, Chun-Yu; Ding, Wen-Cheng; Chen, Chia-Hsun; Chien, Da-Chen; Kuo, Ya-Pei; Chen, Peng-Yu; Lu, Hsueh-Hsing; Chiu, Tien-Lung; Lin, Bo-Yen; Lee, Jiun-Haw
Abstract : In this work, green top emission quantum dot light‐emitting diodes with different structure, that are normal and inverted structure, were demonstrated. The device characterization of these two device are compared. The QLED with inverted structure exhibits better device performance than normal one. Current efficiency is improved from 26.9 to 42.5 cd/A, as well as the external quantum efficiency is improved from 5.32 to 9.42 %. Operational lifetime of inverted structure is longer and more reliable than normal structure by 10‐times.